Ionophore-Assisted Electrochemistry of Neutral Molecules: Oxidation of Hydrogen in an Ionic Liquid Electrolyte - Wandt, J.; Lee, Juni; Arrigan, Damien; Silvester-Dean, Debbie (AMER CHEMICAL SOC, 2019)
Copyright © 2019 American Chemical Society. The electrochemical properties of gas molecules are of great interest for both fundamental and applied research. In this study, we introduce a novel concept to systematically alter the electrochemical behavior and, in particular, the redox potential of neutral gas molecules. The concept is based on the use of an ion-binding agent, or "ionophore", to bind and stabilize the ionic electrochemical reaction product. We demonstrate that the ionophore-assisted electrochemical oxidation of hydrogen in a room-temperature ionic liquid electrolyte is shifted by almost 1 V toward more negative potentials in comparison to an ionophore-free electrolyte. The altered electrochemical response in the presence of the ionophore not only yields insights into the reaction mechanism but also can be used to determine the diffusion coefficient of the ionophore species. This ionophore-modulated electrochemistry of neutral gas molecules opens up new avenues for the development of highly selective electrochemical sensors.